The indigenous book Puratig, the sacred oarand its folk-related narratives (Revista Internacional de Folkcomunicação, 2019)
In an attempt to cover a little about the reality of non-urban non-urban information and communication, not aligned with the thinking of the victorious West, of biased colonization, we propose an analysis of how the informational treatment contained in a book of the work of Yaguaré Yamán. The work Puratig: the sacred oar, by the writer, deals with a totemic instrument, the Puratig (or Porantim), placed by the Sateré-Mawé people as a touchstone, as a philosophical amulet of ethnicity, being the protection historically marked by them to guide precepts of solidarity and brotherhood, as well as justice, encompassing rights and duties. For the analysis of the work, we use evaluative and inferential methodology, which we describe based on the contingencies that the research bequeathed. Indigenous book; Folkcommunication; Amazon.